2021
DOI: 10.1111/bcp.14831
|View full text |Cite
|
Sign up to set email alerts
|

Liver and kidney function in patients with Covid‐19 treated with remdesivir

Abstract: For the treatment of Covid‐19 patients with remdesivir, poor renal and liver function were both exclusion criteria in randomized clinical trials and contraindication for treatment. Also, nephrotoxicity and hepatotoxicity are reported as adverse events. We retrospectively reviewed renal and liver functions of Covid‐19 103 patients who received remdesivir in the 15 days after treatment initiation. Approximately 20% of the patient population met randomized clinical trial exclusion criteria. In total, 11% of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 12 publications
6
32
0
Order By: Relevance
“…There are also other studies that have found liver function test abnormalities in remdesivir-treated COVID-19 patients with 23% of patients with elevated liver enzymes in a case series (n = 53) [40], and elevated serum aminotransferases and total bilirubin in 5% and 10% respectively of COVID-19 patients in a multicenter, randomized, double-blind, placebo-controlled study [41]. Finally, in a recently retrospective study of 103 COVID-19 patients, 35% of participants had increased AST and 25% elevated ALT levels indicating the hepatotoxic effect of remdesivir therapy [42].…”
Section: Remdesivirmentioning
confidence: 98%
“…There are also other studies that have found liver function test abnormalities in remdesivir-treated COVID-19 patients with 23% of patients with elevated liver enzymes in a case series (n = 53) [40], and elevated serum aminotransferases and total bilirubin in 5% and 10% respectively of COVID-19 patients in a multicenter, randomized, double-blind, placebo-controlled study [41]. Finally, in a recently retrospective study of 103 COVID-19 patients, 35% of participants had increased AST and 25% elevated ALT levels indicating the hepatotoxic effect of remdesivir therapy [42].…”
Section: Remdesivirmentioning
confidence: 98%
“…There are also other studies that have found liver function test abnormalities in remdesivir-treated COVID-19 patients with 23% of patients with elevated liver enzymes in a case series (n = 53) [66], and elevated serum aminotransferases and total bilirubin in 5% and 10% of COVID-19 patients in a multicenter, randomized, double-blind, placebo-controlled study [67]. Finally, in a recently retrospective study of 103 COVID-19 patients, 35% of participants had increased AST and 25% elevated ALT levels indicating the hepatotoxic effect of remdesivir therapy [68].…”
Section: Remdesivirmentioning
confidence: 98%
“…Furthermore, the use of an electronic health record text mining tool has proven to be helpful in tracking adverse events. More studies have been published using CTcue or a comparable tool to retrieve data from the EHR, including a validation study 27 , 30 , 31 . In the future, in case of a suspicion of the occurrence of a specific adverse event, a text mining tool can efficiently extract data from EHRs and can therefore quickly provide clarity on the relationship with the use of a particular drug.…”
Section: Discussionmentioning
confidence: 99%